The Information Content of SEC Filings and Investor Sophistication: A Variance Decomposition Analysis - SEGAL, Dan (Institutional Knowledge at Singapore Management University, 2006)
Using the Vuolteenaho (2002) variance decomposition methodology, this study assesses the relative value relevance of cash flow, accrual, and expected return news on SEC and preliminary earnings filing dates, as measured by their contribution to the volatility of unexpected returns. Cashflow news is found to be more valuerelevant than accrual news. Although expected return (risk) news is the least valuerelevant, it is significantly correlated with changes in betas and returns at the preliminary and SEC filing dates, indicating association with changes in firm risk and discount rates. This study also documents that these informational components contain less (more) value-relevant information at the SEC filing date for firms with a higherproportion of long-term (short-term) sophisticated investors after controlling for other dimensions of the information environment.